Device Characteristics of Top-Emitting Organic Light-Emitting Diodes Depending on Anode Materials for CMOS-Based OLED Microdisplays - Hyunkoo Lee; Hyunsu Cho; Chun-Won Byun; Chan-Mo Kang; Jun-Han Han; Jeong-Ik Lee; Hokwon Kim; Jeong Hwan Lee; Minseok Kim; Nam Sung Cho (IEEE Photonics Journal, 2018)
We investigated the optical reflectance, surface roughness, and sheet resistance of aluminum (Al)/titanium nitride (TiN), titanium (Ti), and tungsten (W) layers on Si substrates, which are available in the CMOS foundry, for organic light-emitting diode (OLED) microdisplays. The devices with different metal anode layers exhibited different hole-injection properties and OLED performances, owing to the different optical and electrical properties of metal anode layers. Based on the OLED characteristics, the Al/TiN layer was selected as an anode layer for OLED microdisplays. A green monochromatic OLED microdisplay panel was designed and implemented using the 0.11-μm CMOS process. The density of pixels was ∼2 351 pixels per inch and the panel's active area was 0.7 in in diagonal. The resolution of the panel was 1 280 × 3 × 1 024, corresponding to SXGA. The panel was successfully operated, and the maximal luminance was ∼460 cd/m2.